Download presentation
1
Derivative Rules
2
power f (x) = ax n so f ' (x) = nax n – 1 Example y = – 5x 3 ,
so y ' = – 15x 2
3
product f (x) = u v, so f '(x) = u' v + v' u Example y = 6x 2 x 8
y ' = 12x ( x 8) + 6x 2 (8x 7) = 60x 9 .
4
quotient
5
chain y = f [g(x)], so y ' = f '[g(x)] g'(x) Example
f(x)=x 3 g(x)= 2x 5 – 7x 2 y ' = 3(2x 5 – 7x 2) 2 (10x 4 – 14x) Calculate the derivative of h(x) = (–3x 2 + 5x – 1) 4
6
Solution 4 (–3x 2 + 5x – 1) 3 (– 6x + 5)
7
Examples h(x)=(2x + 7) 3 (4x – 3) 5 h(x)=– 3(x 5 + 7x 3 + 2x – 17) 15
h’(x)=3(2x + 7) 2 (2)(4x – 3) 5 + 5(4x – 3) 4 (4)(2x + 7) 3 h(x)=– 3(x 5 + 7x 3 + 2x – 17) 15 h’(x)= – 45(x 5 + 7x 3 + 2x – 17) 14 (5x x 2 + 2)
8
Log function Example y = ln (5x 3 – 4x 2 + 3x)
9
log a u Derivative = Example y = log 3 (4x 3 – 6x + 1)
10
Exponential functions
f(u) = (e u) so f’(u)= du e u f(u)= (a u ) so f’(u)= du a u ln a Example y = ( 3 ) 2 x – 5, y ' = 2(3) 2 x – 5 ln 3, (it's du a u ln a)
11
Trig derivatives Function derivative sin u du cos u cos u – du sin u
Practice y=– 5cos 4(3x+1) y = – 3 sin 2 5x
12
Solution y’= 20(3) cos 3 (3x+1) sin (3x+1) (chain rule)
y ' = – 6 (5) sin 5x cos 5x
13
Practice e2x + 3 ex² esin x. esin x cos x e−x −e−x x²ex
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.